Atomistic-scale simulations of the chemomechanical behavior of graphene under nanoprojectile impact. (April 2016) - Yoon, Kichul; Ostadhossein, Alireza; van Duin, Adri C.T.
Abstract: Despite its importance, the mechanical behavior of graphene under the impact of projectiles has rarely been studied due to experimental and computational difficulties. Here, we simulated the impact of silica and nickel projectiles with a supersonic initial velocity on graphene. Then we analyzed the impact by using ReaxFF reactive force field method, which is capable of describing the entire system. During the process of projectile penetration, we identified various atomistic features, such as the formation of pentagon/heptagon pairs at the edges of the cracks, and the preferential crack edges that are affected by the deformability of graphene before crack initiation. Effects of defects in graphene and the material type of the projectile on specific penetration energy ( E p * ) also were addressed. The values of E p * obtained in our simulations were in general agreement with the recent experimental values reported by Lee et al. [ Science 2014, 346, (6213), 1092–1096]. Our simulation results showed that E p * was correlated with the diameter of maximum deformation of graphene before crack initiation, demonstrating the superior E p * of graphene as a result of its high ultimate stress and strain. Graphical abstract: